The risks of telehealth in radiation oncology: challenges and mitigation strategies - Stathakis, Sotiri; Papanikolaou, Niko; Ashford, Jessica; Stephens, Jason; LaRose, Aaron (Frontiers in Oncology, 2025)
The integration of telehealth into radiation oncology represents a significant evolution in healthcare delivery, driven by the potential for enhanced patient accessibility, convenience, and improved multidisciplinary collaboration and operational efficiency. Telehealth modalities support a wide range of activities, from remote consultations and treatment planning discussions to on-treatment checks, toxicity management, and follow-up care. However, the successful adoption of telehealth is predicated upon the effective identification and management of substantial challenges. These include safeguarding sensitive patient data against cybersecurity threats, navigating the inherent limitations of remote clinical assessments, overcoming technological barriers that contribute to the digital divide, adhering to a complex and evolving regulatory and reimbursement environment, maintaining the crucial therapeutic patient-provider relationship, seamlessly integrating telehealth workflows into existing clinical operations, and upholding ethical principles, particularly concerning equitable access and algorithmic bias. While initial concerns about potential risks, such as increased rates of misdiagnosis or reduced patient satisfaction, were prominent during the early phase of rapid adoption, a growing body of recent empirical literature provides valuable insights into the actual impact of telehealth in radiation oncology and the effectiveness of various mitigation strategies. This paper offers a comprehensive and updated review of these multifaceted challenges, analyzing their potential influence on clinical outcomes, healthcare operations, and the patient experience. Drawing upon the latest evidence, it details proactive, evidence-based mitigation strategies – encompassing the strategic implementation of hybrid care models, investments in secure and user-friendly technological infrastructure, the development and adherence to standardized clinical and operational protocols, targeted training for providers and staff, and robust support mechanisms for patients. A structured, continuous risk management framework is presented as an essential component for navigating these complexities. By thoroughly understanding these challenges and actively implementing evidence-informed mitigation approaches, radiation oncology practices can successfully harness the considerable benefits of telehealth while rigorously protecting patient safety, ensuring the delivery of high-quality care, and promoting equitable access to cancer treatment for all individuals.